2008
DOI: 10.1073/pnas.0806152105
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic nucleotide phosphodiesterase profiling reveals increased expression of phosphodiesterase 7B in chronic lymphocytic leukemia

Abstract: Cyclic nucleotide phosphodiesterase (PDE) isoforms can influence disease pathogenesis and be novel therapeutic targets. Because lower cAMP levels may contribute to the decreased apoptosis that occurs in chronic lymphocytic leukemia (CLL), we assessed the expression levels of PDE isoforms in peripheral blood mononuclear cells (PBMC) of healthy adults and patients with CLL. We found a unique PDE mRNA signature in CLL: higher levels than in normal PBMC of PDE7B (increased Ϸ23-fold) and lower levels of PDE3B, 4D, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 45 publications
4
89
0
Order By: Relevance
“…These data indicate that these PDEs do not contribute significant cAMP hydrolysis in DLBCL. In addition, in agreement with earlier work, 18,19 but contrary to a recent report in chronic lymphoid leukemia (CLL), 20 we found that PDE7B is not expressed in lymphoid cells (DLBCL) and that the PDE7-specific inhibitor BRL-50481 is largely ineffective in DLBCL cell lines (data not shown). These data suggested that the observed cAMP-mediated inhibition of SYK is directly controlled by PDE4B expression/activity.…”
Section: Camp Inhibits Syk Activity In Normal B Cellssupporting
confidence: 93%
“…These data indicate that these PDEs do not contribute significant cAMP hydrolysis in DLBCL. In addition, in agreement with earlier work, 18,19 but contrary to a recent report in chronic lymphoid leukemia (CLL), 20 we found that PDE7B is not expressed in lymphoid cells (DLBCL) and that the PDE7-specific inhibitor BRL-50481 is largely ineffective in DLBCL cell lines (data not shown). These data suggested that the observed cAMP-mediated inhibition of SYK is directly controlled by PDE4B expression/activity.…”
Section: Camp Inhibits Syk Activity In Normal B Cellssupporting
confidence: 93%
“…Expression of PDE7B mRNA and protein in peripheral blood mononuclear cells from patients with chronic lymphocytic leukemia is greatly increased compared with cells from healthy individuals (428). PDE7B activity accounts for a greater portion of the cAMP-hydrolyzing activity in these cells, whereas levels of mRNA for PDEs 3B and 4D are reduced.…”
Section: Regulation Of Pde7mentioning
confidence: 91%
“…[4][5][6][7] The impairment of cyclic adenosine monophosphate (cAMP) or cyclic guanosine monophosphate (cGMP) generation by regulation of phosphodiesterases (PDEs) has been implicated in various cancer pathologies. 8,9 PDEs are enzymes that regulate cellular levels of cAMP/cGMP by controlling their degradation. These enzymes are classified into 11 families (PDE1-PDE11) based on their sequence similarity, substrate preference and sensitivity to various inhibitors.…”
Section: Introductionmentioning
confidence: 99%